Risk factors associated with metabolic syndrome in bipolar and schizophrenia subjects treated with antipsychotics: the role of folate pharmacogenetics - Ellingrod, Vicki L; Taylor, Stephan F; Dalack, Gregory; Grove, Tyler B; Bly, Michael J; Brook, Robert D; Zöllner, Sebastian K; Pop-Busui, Rodica (Journal of clinical psychopharmacology, 2012)
Folate has been implicated in cardiovascular disease with atypical antipsychotic (AAPs) use, and individuals with methylenetetrahydrofolate reductase (MTHFR) and catechol-O-methyl transferase (COMT) variants are at greater risk. This study examined the relationship between the MTHFR 677C/T, MTHFR 1298A/C, and COMT Val158Met variants; metabolic syndrome; and lifestyle measures in schizophrenia and bipolar subjects. A total of 237 subjects with bipolar or schizophrenia receiving an antipsychotic for at least 6 months were included in this cross-sectional analysis. Subjects were screened for the metabolic syndrome (National Cholesterol Education Program Adult Treatment Panel III criteria) and MTHFR 677C/T, MTHFR 1298A/C, and Val158Met genotypes. In addition, serum folate and homocysteine were measured along with lifestyle factors. The subject's mean age was 44.7 (SD, 11.7) years; 72% were white, and 51% male; 61% were receiving an AAP; the mean body mass index was 32.6 (SD, 8.2) kg/m, and 48% were current smokers. Overall, 41% met metabolic syndrome criteria (n = 98). There were no differences in age, sex, AAP exposure, or body mass index between genotype groups. Metabolic syndrome was related to age, smoking, and the MTHFR 677T and COMT 158Val alleles (χ = 34.4, P < 0.0001). In addition, AAP use showed a trend association with metabolic syndrome (χ = 3.21, P = 0.07). These data support our previous reports and add more data pointing to folate's role in mediating a link between mental illness and cardiovascular disease. Use of this information clinically may help to reduce the risk for AAP metabolic complications in those whose clinical care necessitates the use of AAPs.